PENGEMBANGAN MEDIA HEALTHY DENTAL BOX (HDB) UNTUK MEMFASILITASI KETERAMPILAN MENGGOSOK GIGI ANAK USIA 4-5 TAHUN - Najiah, Irna; Nur, Lutfi; Rahman, Taopik (Universitas Pendidikan Indonesia (UPI), 2020)
This research is based on the results of preliminary studies that have been conducted by researchers regarding the importance of brushing teeth. Brushing teeth in children aged 4-5 years is not explained in detail in the curriculum and has an impact on the difficulties faced by teachers in selecting and designing learning media to brush their teeth, therefore researchers design learning media with approaches that are appropriate to the conditions of children in the field. Researchers developed the tooth puppet media into a Healthy Dental Box (HDB) medium to facilitate the brushing skills of children aged 4-5 years. The method used in this research is Design Based Research (DBR) developed by Reeves to design, develop, and test the feasibility of a product to overcome problems in learning. Data collection is done by observation, interview and validation of media experts. In general, the product is declared suitable for use as a learning medium regarding brushing teeth based on the results of media validation by experts in the health sector, experts in the field of learning media and pedagogical experts. Reflections on product development, namely producing Healthy Dental Box (HDB) media to facilitate tooth brushing skills in children aged 4-5 years.Â Penelitian ini didasarkan pada hasil studi pendahuluan yang telah dilakukan oleh peneliti mengenai pentingnya menggosok gigi. Menggosok gigi pada anak usia 4-5 tahun tidak dijelaskan secara rinci dalam kurikulum dan berdampak pada kesulitan yang dihadapi guru dalam memilih dan merancang media pembelajaran menggosok gigi anak, untuk itu peneliti merancang media pembelajaran dengan pendekatan yang sesuai dengan kondisi anak di lapangan. Peneliti mengembangkan media boneka gigi menjadi media Healthy Dental Box (HDB) untuk memfasilitasi keterampilan menggosok gigi anak usia 4-5 tahun. Metode yang digunakan dalam penelitian ini adalah Design Based Research (DBR) yang dikembangkan oleh Reeves untuk merancang, mengembangkan, dan menguji kelayakan suatu produk untuk mengatasi masalah dalam pembelajaran. Â Â Pengumpulan data dilakukan dengan observasi, wawancara dan validasi ahli media. Secara umum produk dinyatakan layak digunakan sebagai media pembelajaran mengenai menggosok gigi berdasarkan hasil validasi media oleh ahli dalam bidang kesehatan, ahli bidang media pembelajaran dan ahli pedagogik. Refleksi dari pengembangan produk, yaitu menghasilkan media Healthy Dental Box (HDB) untuk memfasilitasi keterampilan menggosok gigi pada anak usia 4-5 tahun.